RUBELA: STRATEGI MEMOTIVASI SISWA DI NAGARI PAUAH DUO NAN BATIGO KECAMATAN PAUAH DUO KABUPATEN SOLOK SELATAN - Nelvia Iryani; Reski Harianti (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
This activity has been held at Nagari Pauah Duo Nan Batigo for 40 days on 29th June until 8th August 2018. Many activities has been carried out together by students college and the comunity of Nagari Pauah Duo Nan Batigo, which was Rubela activity (Learning house). This paper aims to describe the activity program carried out by Pauah Duo Nan Batigo KKN students namely the Rubela activity ( Learning house). This activity was motivated by the students lack of understanding about the importance of education so that the students were less interested to continue their education to the higher level. The method used in the activity was the method of public education in the form of councelling and socialization. The activity was carried out four times per week with a delivery of material for several classes and the discussion of the excercises and homeworks with the students. All varies out activities got positive responses from the participants, public society, and comunity leaders. KKN program besides as a learning method for college students, it is also an effort of Andalas Universitiy to contibute in transforming the value of education to the public comunity.